Direct comparison of radioimmunoassay and LC–MS/MS for PK assessment of insulin glargine in clinical development. (December 2014) - Xu, Yang; Prohn, Marita; Cai, Xiaoyan; Crutchlow, Michael; Shankar, Sudha S; Bateman, Kevin; Woolf, Eric J
Background: A direct comparison of radioimmunoassay (RIA) and LC–MS/MS for insulin glargine quantification in human plasma is provided.Results: Compared with the RIA, the LC–MS/MS assay exhibited comparable/improved sensitivity (LLOQ at 0.1 ng/ml [˜16.7 pM or 2.8 μU/ml] for glargine and its metabolites M1 and M2, respectively) and ruggedness. Most importantly, it demonstrated a superior specificity advantage against the interference from endogenous insulin, exogenous insulin analogs (e.g., Novolog ®, Humalog ® or Levemir ®, routine treatment for diabetes mellitus) and potentially pre-existing anti-insulin antibodies in patient samples. The data obtained from diabetic patients suggested the LC–MS/MS assay substantially improved pharmacokinetic characterization of glargine.Conclusion: LC–MS/MS overcame common limitations of RIA, and provided critically needed specificity to support glargine clinical development, without sacrificing assay sensitivity and ruggedness.